Construction of a High-Temperature Sensor for Industry Based on Optical Fibers and Ruby Crystal - Hercík, Radim; Mikolajek, Martin; Byrtus, Radek; Hejduk, Stanislav; Látal, Jan; Vanderka, Aleš; Macháček, Zdeněk; Koziorek, Jiří (Sensors (Basel, Switzerland), 2024)
This paper presents the construction of an innovative high-temperature sensor based on the optical principle. The sensor is designed especially for the measurement of exhaust gases with a temperature range of up to +850 °C. The methodology is based on two principles-luminescence and dark body radiation. The core of this study is the description of sensing element construction together with electronics and the system of photodiode dark current compensation. An advantage of this optical-based system is its immunity to strong magnetic fields. This study also discusses results achieved and further steps. The solution is covered by a European Patent.